Secrecy as Pauline Influence on the Gospel of Mark - Wendt, Heidi (Journal of Biblical literature, 2021)
This article bridges two substantial but historically distinct bodies of scholarship on the Gospel of Mark: investigation of its multiple secrecy motifs, on the one hand, and its alleged "Paulinism," on the other. Recent decades have seen renewed interest in exploring a possible relationship between Paul and the earliest gospel, whether attributed to its general conformity with "Pauline Christianity" or to the author's specific knowledge of Pauline letters. Despite being a prominent topic in other scholarship on Mark, however, secrecy has received little sustained attention with respect to the question of Pauline influence. I address this lacuna by amplifying the many theological affinities between the texts while also exploring Mark's secrecy as a narrative strategy whose elements cooperate to privilege Paul as the principal (or only) authority on Christ. I then broach the implications of my reading for the gospel's early reception, offering preliminary theorization of intellectual dynamics it fostered and in which settings these may have resonated.